Preparation and Application of a Novel Adhesive (Copolymer Compound) - Khazaei, Ardeshir; Ghorbani Waghei, Ramini (Asian Journal of Chemistry, 2010)
A novel adhesive compound was synthesised by reaction of bromosul-fonamide with methylmethacrylate in ambient temperature. The novel adhesive is stable and not hygroscopic.